Influence Competence Apparatus and Utilization Technology Information on management performance goods with quality Goods Administration as an Intervening Variable - Sri Purwanti; Anita Jitmau (Proceeding of The International Conference on Business and Economics, 2026)
Administration of Regional Assets (BMD) is one of the important activities in managing regional assets. Good quality administration requires competent personnel and adequate information technology support. This study aims to analyze the influence of personnel competence and the use of information technology on the quality of BMD administration , with asset management performance as an intervening variable . The research method uses a quantitative approach through a survey of personnel directly involved in managing regional assets. The results show that personnel competence and the use of information technology have a positive effect on asset management performance and directly on the quality of BMD administration . In addition, asset management performance is proven to significantly mediate the relationship between the two independent variables and the quality of BMD administration . This finding emphasizes the importance of increasing the capacity of personnel and optimizing the use of Information Technology in creating accurate, transparent, and accountable regional asset governance . The quality indicators of goods administration in this study are the accuracy of asset recording, completeness of goods documents and data, timeliness of reporting, conformity of physical data with administrative data, compliance with administration regulations .